Bulgaria : Financial System Stability Assessment-Press Release; Staff Report; and Statement by the Executive Director for Bulgaria. (IMF Staff Country Reports; Country Report, 2017)
This paper assesses the stability of the financial system in Bulgaria. Progress has been made in Bulgaria to strengthen supervision since the 2015 Basel Core Principles assessment, but more work and resources are needed. A more targeted strategy is needed to address high nonperforming loans (NPLs), which in Bulgaria's banks stood at 13.7 percent of total loans as of June 2016-against the European Union-weighted average of 5.5 percent. Certain accounting, collateral valuation, and risk management practices have discouraged NPL reduction. Banks will also need to build provisions in preparation for the implementation of the forthcoming expected credit loss provisioning standards beginning in 2018.